Export curbs on essential goods in the wake of Covid-19 and the least developed countries: Permanent scarring from a temporary outburst - Simon J. Evenett (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Anything that jeopardises progress towards the Sustainable Development Goals - such as a global pandemic and how governments react to it - is thus a major source of concern, in particular for least developed countries (LDCs). The first half of 2020 witnessed governments imposing dozens of export curbs on essential medical goods and foods that the LDCs, among other nations, depend upon. Although some of those curbs have subsequently been removed, there is a substantial risk of a permanent reduction in essential goods supplied to LDC markets, as current multilateral trade disciplines on export controls do not specifically require a return to the pre-pandemic status quo. Let us not forget that the G20 trade and investment ministers declared on 3 November 2020 that "any emergency trade measures designed to tackle COVID-19, including export restrictions on vital medical supplies and equipment and other essential goods and services, if deemed necessary, are targeted, proportionate, transparent, temporary, reflect our interest in protecting the most vulnerable, do not create unnecessary barriers to trade or disruption to global supply chains, and are consistent with WTO rules" (G20, 2020). Evidence on resort to export restrictions suggests, however, that G20 fealty to this pledge was uneven. The purpose of this Briefing Paper is to outline the key policy developments implicating the trade in essential goods during the first nine months of the COVID-19 pandemic before drawing out the implications for development policy and trade policy cooperation. These lessons need to be taken on board quickly if the mistakes made in 2020 are not to be repeated in 2021, when policymakers and the private sector around the world face the imperative of the equitable and efficient global distribution of COVID-19 vaccines. Recent export controls on such vaccines suggest important lessons from last year have not been taken on board universally. The key findings and policy recommendations are: Permanent disruption to trade routes in medical goods and medicines cannot be ruled out as a result of temporary export curbs. Revisit the World Trade Organization (WTO) rules that allow export curbs during emergencies. LDCs should increase their buying power by joining together to buy medical goods and medicines from a diversified set of production locations. Such buying power would be multiplied if LDCs joined forces with leading development agencies and the multilateral development banks. Stockpiling in advance of any future pandemic offers no cast-iron guarantee, as no-one can know for sure what medical goods will be in high demand.
Keywords: 330